A short decision time for transcatheter embolization can better associate mortality in patients with pelvic fracture: a retrospective study - Mizuno, Yosuke; Miyake, Takahito; Okada, Hideshi; Ishihara, Takuma; Kanda, Norihide; Ichihashi, Masahiro; Kamidani, Ryo; Fukuta, Tetsuya; Yoshida, Takahiro; Nagata, Shoma; Kawada, Hiroshi; Matsuo, Masayuki; et al. (Frontiers in Medicine, 2024)
Background Early use of hemostasis strategies, transcatheter arterial embolization (TAE) is critical in cases of pelvic injury because of the risk of hemorrhagic shock and other fatal injuries. We investigated the influence of delays in TAE administration on mortality. Methods Patients admitted to the Advanced Critical Care Center at Gifu University with pelvic injury between January 2008 and December 2019, and who underwent acute TAE, were retrospectively enrolled. The time from when the doctor decided to administer TAE to the start of TAE (needling time) was defined as “decision-TAE time.” Results We included 158 patients, of whom 23 patients died. The median decision-TAE time was 59.5 min. Kaplan–Meier curves for overall survival were compared between patients with decision-TAE time above and below the median cutoff value; survival was significantly better for patients with values below the median cutoff value (p = 0.020). Multivariable Cox proportional hazards regression analysis revealed that the longer the decision-TAE time, the higher the risk of mortality (p = 0.031). TAE duration modified the association between decision-TAE time and overall survival (p = 0.109), as shorter TAE duration (procedure time) was associated with the best survival rate (p for interaction = 0.109). Conclusion Decision-TAE time may play a key role in establishing resuscitation procedures in patients with pelvic fracture, and efforts to shorten this time should be pursued.